The Impact of Different Innovation Modes on Export Performance of Chinese Firms - Yin, Mingxi; Liang, Zheng (Journal of Applied Business and Economics, 2022)
A growing number of Chinese firms have chosen to enter the export market to benefit from the global market. The analysis of determinants of export performance has become significantly crucial within the context of emerging markets. This study looks at two aspects of innovation strategy, namely internal and external innovation and their effects on exports, which is the first step of internationalization. Drawing on the resource-based view (RBV) and institutional-based view (IBV), the study investigates the role of different innovation modes in shaping the export performance of Chinese firms in the presence of institutional obstacles. The findings show external innovation strategy enables Chinese firms to perform better in the export market. However, the export performance will be negatively affected if firms adopt both innovation strategies. In Tsinghua University’s addition, the impact of the external innovation model is amplified for firms that encounter more institutional obstacles.